Mental Workload and Work Factors as Predictors of Stress Levels in Port Sector Employees - Wahdah Dhiyaul Akrimah; Irlangga Wisnu Wardana; Abdul Rohim Tualeka (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Non-operational employees of the Terminal Jamrud Surabaya are faced with various work-related issues while performing their duties which can be stressful due to work demands, relationships with many parties, and workloads. This study analyzes the relationship between mental workload and work factors (role ambiguity, role conflict, job insecurity, and interpersonal conflict) with occupational stress for non-operational office employees at Terminal Jamrud Surabaya. Methods: This study was a descriptive observational study with a cross-sectional design. The sampling technique used in this study is total sampling. The sample for this study were all employees of the Terminal Jamrud Surabaya office, up to 30 people. Primary data were collected using a questionnaire to assess stress levels and work factors variables. The mental workload was measured using the NASA - Task Load Index questionnaire. Results: The employees mostly have a mental workload, role ambiguity, role conflict, and interpersonal conflict in the moderate category, while the majority of office employees have job insecurity at a low level. Meanwhile, the stress levels felt by employees were mainly in the moderate category. The strong relationship between mental workload with occupational stress is 0.634, while work factors with stress levels consist of role ambiguity (r=0.523), role conflict (r=0.468), job insecurity (r=0.075), and interpersonal conflict (r=0.445). Conclusion: Variables that have a strong relationship are mental workload variables with stress levels in non-operational office employees at Terminal Jamrud Surabaya, PT Pelabuhan Indonesia III.